Genetic variation and cryptic lineage among the sergestid shrimp Acetes americanus (Decapoda) - Simões, Sabrina Morilhas [UNESP]; Costa, Rogério Caetano [UNESP]; Carvalho, Fabricio Lopes; Carvalho-Batista, Abner; de Souza Alves Teodoro, Sarah; Mantelatto, Fernando L. (PeerJ, 2023)
The taxonomic status of the sergestid shrimp, Acetes americanus, has been questioned for several decades. No specific study has been performed thus far to resolve the incongruences. This species has a wide geographical range in the western Atlantic and is represented by two formally accepted subspecies: Acetes americanus carolinae, distributed in North America, and Acetes americanus americanus, present in South America. However, there are regions where the coexistence of both subspecies has been reported, such as Central America. This study aimed to genetically compare specimens of A. a. americanus collected in South America with A. a. carolinae sampled in North America to check for possible differences and the existence of more than one subspecies of A. americanus on the Brazilian coast. Based on the sequences of two informative markers, the cytochrome oxidase I region (COI) and 16S rRNA, phylogenetic reconstruction demonstrated well-defined clades with high support values, reinforcing the idea that A. a. americanus is genetically different from A. a. carolinae. Our hypothesis was corroborated as the specimens collected in Brazil were divided into two distinct lineages: the first composed of A. a. americanus sensu stricto (Brazil 1) and the second by Acetes americanus (Brazil 2). The three groups evidenced in the haplotype network were the same as those observed in the phylogenetic tree. The morphometric character (height/length of the thelycum) was effective in distinguishing A. a. Brazil 1 from A. a. carolinae. However, more detailed and conclusive studies comprising other characteristics to propose and describe a possible new entity are necessary. To the best of our knowledge, for the first time, the results of this study provide some insights into the taxonomic status of the sergestid shrimp A. americanus in the western Atlantic.
Keywords: 16S rDNA; Crustacea; Cytochrome Oxidase I (COI); Molecular phylogeny; Phylogenetics; Sergestidae; Sergestoidea; Western Atlantic